JavaScript: Ajax and Fetch. - Vodnik, Sasha (linkedin.com, 2024)
Ajax is the backbone of high-performance web apps. Learn how to use vanilla JavaScript, Ajax, and APIs like Fetch to request and handle data and modify webpage content.